2007
DOI: 10.1889/1.2759554
|View full text |Cite
|
Sign up to set email alerts
|

All‐additive ink‐jet‐printed display backplanes: Materials development and integration

Abstract: Abstract— Methods used to deposit and integrate solution‐processed materials to fabricate TFT backplanes by ink‐jet printing are discussed. Thematerials studied allow the development of an all‐additive process in which materials are deposited only where their functionality is required. The metal layer and semiconductor are printed, and the solution‐processed dielectric is spin‐coated. Silver nanoparticles are used as gate and datametals, the semiconductor used is a polythiophene derivative (PQT‐12), and the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 23 publications
0
47
0
1
Order By: Relevance
“…Abdou et al [43] studied the interaction of oxygen with conjugated polymers and observed that oxygen forms a reversible charge transfer complex (CTC) with the polymer. It was suggested that CTC is largely responsible for the generation of charge carriers in semiconducting π-conjugated polymers when exposed to air, which modulated the electronic properties of the polymer.…”
Section: N-type Semiconductorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Abdou et al [43] studied the interaction of oxygen with conjugated polymers and observed that oxygen forms a reversible charge transfer complex (CTC) with the polymer. It was suggested that CTC is largely responsible for the generation of charge carriers in semiconducting π-conjugated polymers when exposed to air, which modulated the electronic properties of the polymer.…”
Section: N-type Semiconductorsmentioning
confidence: 99%
“…Analysis of P3HT OTFTs under increasing pressures of oxygen revealed that the formation of CTC resulted in an increase in carrier concentration, increase in conductivity, and decrease in charge carrier mobility. With prolonged or higher intensity exposure of oxygen, the proper transistor behavior was lost [43]. The degree of carrier generation by oxidative doping upon air exposure is expected to increase as the ionization potential (IP) of the polymer is lowered.…”
Section: N-type Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Printed electronics are gaining attention as a technology that enables various electric devices such as organic thin film transistors (OTFTs) [1,2,3], RF-ID tags [4] and sensors [5] to be fabricated using printing process. Printing method has potential of low cost, low environmental impact and large area fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…This is evident also as thick rings at the edges of the drop, commonly referred to as the "coffee-stain" effect [14,15]. The starting point is the research done by research groups [11][12][13][14]16,17] to solve this problem by use of a mixed solvent system. By using a mixed solvent system besides the existence of a convective flow in the drying droplet, there is the creation of a Marangoni flow due to the difference in boiling points and surface tension of the solvents.…”
Section: Introductionmentioning
confidence: 99%